2001
DOI: 10.1097/00005537-200101000-00002
|View full text |Cite
|
Sign up to set email alerts
|

The Diagnosis of a Conductive Olfactory Loss

Abstract: The etiology for olfactory loss can in many cases be difficult to determine, but it is important to establish prognosis and to predict response to therapy. Diagnosis requires a thorough history, appropriate chemosensory testing, and a physical examination that should include nasal endoscopy. A trial of systemic steroids may serve to verify that the loss is indeed conductive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

9
187
1
13

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 203 publications
(213 citation statements)
references
References 16 publications
9
187
1
13
Order By: Relevance
“…Upper respiratory infections (URI), especially viral, and sinonasal diseases (allergic rhinitis, chronic rhinosinusitis with or without nasal polyps, sinonasal benign or malignant tumors) together are responsible for 32 to 72% of olfactory disorders, depending on the chosen studies. Sinonasal diseases alone are responsible for 14% of olfactory disorders [2,3].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Upper respiratory infections (URI), especially viral, and sinonasal diseases (allergic rhinitis, chronic rhinosinusitis with or without nasal polyps, sinonasal benign or malignant tumors) together are responsible for 32 to 72% of olfactory disorders, depending on the chosen studies. Sinonasal diseases alone are responsible for 14% of olfactory disorders [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…The physical examination should include a complete head and neck examination, with a special attention given to nasal endoscopy [5]. Seiden et al [2] showed that anterior rhinoscopy alone was only able to diagnose sinonasal disease as a cause of smell loss in 51% of patients with the disease, while nasal endoscopy missed the diagnosis in 9% [2,3,5]. Isolated septal deviation and moderate turbinate hypertrophy are of limited predictive value finding a etiology for smell loss [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, CRS is described as the most common cause of olfactory dysfunction, accounting for 14-30% of cases (Holbrook and Leopold 2006;Mott and Leopold, 1991;Raviv and Kern 2004;Seiden and Duncan, 2001). Inversely, olfactory impairment is a common symptom affecting 61-83% of patients with CRS (Bhattacharyya, 2003;Litvak et al, 2008;Orlandi and Terrell, 2002;Soler et al, 2008).…”
mentioning
confidence: 99%
“…Nevertheless up to one quarter of patients with CRS are unaware of their decreased olfactory abilities, probably because the olfactory dysfunction in CRS develops slowly and in consequence only a few patients note this disorder (Nordin et al, 1995). Psychophysical tests results show that patients with CRS have quantitative disorders, between hyposmia and anosmia (Holbrook and Leopold 2006;Mott and Leopold, 1991;Raviv and Kern 2004;Seiden and Duncan, 2001;Welge-Luessen, 2009) and may report fluctuating symptoms (Apter et al, 1999). Also it is widely known that patients with CRS with polyps have a higher incidence of smell symptoms and anosmia than patients with CRS without polyps (Hellings and Rombaux, 2009).…”
mentioning
confidence: 99%